2014
DOI: 10.1007/s10339-014-0627-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulation by three-dimensional natural images on prefrontal cortex and autonomic nerve activity: a comparison with stimulation using two-dimensional images

Abstract: Empirical evidence suggests that three-dimensional (3D) images of nature promote physiological relaxation in humans by providing more realistic effects compared with two-dimensional (2D) images. However, no studies have evaluated the physiological relaxation effects of nature-derived 3D images on prefrontal cortex and autonomic nerve activity. The present study aimed to clarify the physiological relaxation effects of visual stimulation by 3D flower images on prefrontal cortex and autonomic nerve activity. Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…There are many cypress in Japan's forests, and the effect of the scent of hinoki, which is found on the Kodo course, can be considered part of the effect of forest bathing [19]. The visual sense of the forest has also been shown to have a relaxing effect [20]. The current study involved walking for a long time and distance, and found the relaxation effect conventionally shown for walking in a forest compared with urban areas.…”
Section: Discussionmentioning
confidence: 58%
“…There are many cypress in Japan's forests, and the effect of the scent of hinoki, which is found on the Kodo course, can be considered part of the effect of forest bathing [19]. The visual sense of the forest has also been shown to have a relaxing effect [20]. The current study involved walking for a long time and distance, and found the relaxation effect conventionally shown for walking in a forest compared with urban areas.…”
Section: Discussionmentioning
confidence: 58%
“…Recent studies have focused on the physiological relaxing effects of nature-derived stimulation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], and there are several reports on the effects of wood odor on humans [9][10][11]. Miyazaki et al [9] reported that inhalation of Taiwan hinoki oil odor decreases systolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that natural environments or nature-derived stimuli, such as forests [36][37][38][39][40][41][42], urban parks [43][44][45], flowers [46][47][48][49][50], and foliage plants [51,52], induce physiological relaxation in humans. Wood is a familiar natural material which we have many opportunities to touch on a daily basis, and it is used for many household objects, such as interior materials of buildings and houses, furniture (desks and shelves), and stationery.…”
Section: Discussionmentioning
confidence: 99%